1994
DOI: 10.1017/s0924933800002285
|View full text |Cite
|
Sign up to set email alerts
|

Platelet serotonin-binding and dexamethasone suppression test in melancholia and dysthymia

Abstract: SummaryPlatelet serotonin-binding (Bmax), using tritiated-seroionin as the ligand, was determined in 75 patients suffering from major depression with melancholia and in 26 patients diagnosed from dysthymic disorder. Twenty-five normal subjects were used as a control group. The melancholic group had significantly lower Bmax values (mean: 6.7 ± 6.1 pmol/108 platelets) than either dysthymic (9.3 ± 3.9 pmol/108 platelets) or control (9.2 ± 4.8 pmol/108 platelets) groups, while there were no significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Studies of biological variables have yet to identify consistent differences between chronic and nonchronic groups. Studies of hypercortisolemia (Gasto et al, 1994;Miller, Norman, & Dow, 1986), growth hormone secretion (Maes, Vandewoude, Maes, Schott, & Cosyns, 1989), sleep physiology (Appelboom-Fondu, Kerkhofs, & Mendlewicz, 1988), and neurotransmitter functioning (Ravindran, Bialik, Brown, & Lapierre, 1994) revealed that the abnormalities in chronic depression are similar to or less pronounced than those found in nonchronic cases (see Riso, Miyatake, & Thase, 2002, for a review). Some evidence has been found for increased rates of subclinical hypothyroidism for subgroups of individuals with chronic depression (Scott, Barker, & Eccleston, 1988;Tappy, Randin, Schwed, Werthermimer, & Memarchand-Beraud, 1987).…”
mentioning
confidence: 99%
“…Studies of biological variables have yet to identify consistent differences between chronic and nonchronic groups. Studies of hypercortisolemia (Gasto et al, 1994;Miller, Norman, & Dow, 1986), growth hormone secretion (Maes, Vandewoude, Maes, Schott, & Cosyns, 1989), sleep physiology (Appelboom-Fondu, Kerkhofs, & Mendlewicz, 1988), and neurotransmitter functioning (Ravindran, Bialik, Brown, & Lapierre, 1994) revealed that the abnormalities in chronic depression are similar to or less pronounced than those found in nonchronic cases (see Riso, Miyatake, & Thase, 2002, for a review). Some evidence has been found for increased rates of subclinical hypothyroidism for subgroups of individuals with chronic depression (Scott, Barker, & Eccleston, 1988;Tappy, Randin, Schwed, Werthermimer, & Memarchand-Beraud, 1987).…”
mentioning
confidence: 99%